Back Cover Image: Volume 3 Issue 1. Issue 1 (30th March 2022) - Abeyweera, Sasitha C.; Simukaitis, Matas; Wei, Qilin; Sun, Yugang
Abstract : Back cover image : Selective synthesis of the liquid commodity from electrochemical reduction of carbon dioxide (CO2 ) is promising to neutralize carbon footprint. Developing the appropriate catalyst to efficiently and selectively promote ethanol formation is challenging because of the involvement of coupling two types of carbon intermediates with different valence values. This work reports the rational design and synthesis of Ag/Cu bimetallic nanostructures with a high density of Ag/Cu interfaced boundaries. The shallowly reduced intermediates (CO) on the Ag surface and the deeply reduced intermediates (CHx ) on the Cu surface simultaneously migrate to the Ag/Cu boundaries and couple into ethanol molecules. The Faradaic efficiency for ethanol formation catalyzed by the synthesized Ag/Cu interfaced nanostructures reaches 50%. (DOI: https://doi.org/10.1002/smm2.1096 )